2019
DOI: 10.1073/pnas.1805928116
|View full text |Cite
|
Sign up to set email alerts
|

Body camera footage leads to lower judgments of intent than dash camera footage

Abstract: SignificanceSurveillance video from body cams and dash cams is increasingly used by police organizations to enhance accountability, and yet little is known about their effects on observer judgment. Across eight experiments, body cam footage produced lower judgments of intent in observers than did dash cam footage, in part, because the body cam (vs. dash cam) visual perspective reduces the visual salience of the focal actor. This research informs public policy regarding the interpretation of video surveillance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 14 publications
5
31
2
Order By: Relevance
“…In our Study 2, linear effect models accounting for four different police encounters revealed that people who viewed BWC footage did not form different beliefs about intent, causality, responsibility, or punishment compared with people who watched the corresponding dash‐cam or bystander recordings. These null results ran counter to our hypotheses and failed to replicate the findings from Study 1 and Turner et al (). Our results are surprising, given that we used two stimuli that the participants of Turner et al () watched and that we asked similar questions about officer intentionality.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In our Study 2, linear effect models accounting for four different police encounters revealed that people who viewed BWC footage did not form different beliefs about intent, causality, responsibility, or punishment compared with people who watched the corresponding dash‐cam or bystander recordings. These null results ran counter to our hypotheses and failed to replicate the findings from Study 1 and Turner et al (). Our results are surprising, given that we used two stimuli that the participants of Turner et al () watched and that we asked similar questions about officer intentionality.…”
Section: Discussioncontrasting
confidence: 99%
“…These null results ran counter to our hypotheses and failed to replicate the findings from Study 1 and Turner et al (). Our results are surprising, given that we used two stimuli that the participants of Turner et al () watched and that we asked similar questions about officer intentionality.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations